Study on metabolic status of tear fluid in hypothyroidism patients with dry eye syndrome (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Dry eye syndrome (DES) is associated with a complicated multifactorial mechanism, the peculiarities of which are being studied at the moment. Data on tear production disorders in hypothyroidism and on disturbances in activity of enzymes providing homeostasis of reduced glutathione in DES underline the need to study metabolic alterations in lacrimal gland function in patients with hypothyroidism.Purpose. To study the character of metabolic alterations in the tear fluid in primary hypothyroidism patients with DES.Material and Methods. We examined 78 patients with primary hypothyroidism. Among the patients, there were 16 subclinical hypothyroidism patients without DES (hypothyroidism-only group) and 62 patients with DES (hypothyroidism+DES group) (hypothyroidism type: subclinical, 32 patients; manifest, 30 patients; hypothyroidism compensation: compensation, 28 patients; subcompensation, 20 patients; decompensation, 14 patients). 16 healthy volunteers served as controls. Results. Hypothyroidism patients had more pronounced biochemical changes in the tear fluid in manifest hypothyroidism with DES and decompensated hypothyroidism: the increased activity of acid phosphatase, lactate dehydrogenase, and malate dehydrogenase; disorders in the thiol status against the background of the increased malondialdehyde level.Conclusions. The increased activity of dehydrogenases and acid phosphatase as well as of malondialdehyde against the background of the decreased thiol status in the tear fluid can testify to destruction in cells and subcellular structures of the corneal epithelium in hypothyroidism accompanied with DES that is caused by the action of both lipid peroxidation products and lysosomal enzymes.
Keywords: hypothyroidism; dry eye syndrome; tear fluid; dehydrogenase; acid phosphatase; thiol status; lipid peroxidation